The role of increased post-impact ball speed on plantar pressure during open and square stance groundstrokes in female tennis players - Johanna Lambrich; Thomas Muehlbauer (BMC, 2024)
Abstract Background It is firmly established that achieving a high ball speed during the execution of groundstrokes represents a relevant factor for success in tennis. However, little is known about how plantar pressure changes as post-impact ball speed is increased during open and square stance groundstrokes. The objective of the study was to determine how tennis players change the plantar pressure in each foot when they execute open versus square stance forehand groundstrokes in order to increase post-impact ball speed. Methods Fifteen healthy female tennis players with ITN 2 or better (mean age: 22.7 ± 7.8 years) participated in this study. The players performed open and square stance longline forehand groundstrokes (topspin) at the following four post-impact ball speed levels: 80 km/h, 90 km/h, 100 km/h, and v max. Flexible pressure-detecting insoles were used to measure plantar pressure in each foot [i.e., dominant (equals the stroke arm) and nondominant]. Results The repeated measures ANOVA showed significant stance style × foot dominance interactions and post-hoc analyses revealed larger maximal and mean forces during open compared to square stance for the dominant but not non-dominant foot. Further, the ball speed × stance style × foot dominance interaction reached the level of significance and post-hoc analyses showed increased/decreased mean forces in the dominant/non-dominant foot during the square but not open stance when players increased their post-impact ball speed. Conclusion Larger values in the open stance, but post-impact ball speed-adjusted values in square stance indicate different advantages in both styles, suggesting their situation-specific application.